2019
DOI: 10.1371/journal.pone.0225654
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of prismatic correction in partially accommodative esotropia

Abstract: PurposeIn partially accommodative esotropia (PAET), prism glasses can correct small angles of residual esotropia but the long-term effect of prismatic correction alone without surgery has not been reported. We aimed to investigate the long-term outcome of prism glasses after full hypermetropic correction for PAET.MethodsThis retrospective, case-control study was performed for children aged 10 years or younger with a residual esotropia of ≤ 20 prism diopters (PD) after full hypermetropic correction who were fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Kenneth et al stated that the amount of muscle that was recessed could be calculated based on the augmentation formula, the sum of deviation of the near without spectacles, and distance deviation with spectacles, divided by 2. [3,[9][10][11]13]. In our patient, the deviation found to be 45∆ (50∆ + 40∆ BO / 2) then the recession is carried out at about 6 mm as shown in the table (Table 1).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Kenneth et al stated that the amount of muscle that was recessed could be calculated based on the augmentation formula, the sum of deviation of the near without spectacles, and distance deviation with spectacles, divided by 2. [3,[9][10][11]13]. In our patient, the deviation found to be 45∆ (50∆ + 40∆ BO / 2) then the recession is carried out at about 6 mm as shown in the table (Table 1).…”
Section: Introductionmentioning
confidence: 73%
“…Hye et alsuggested a minimum follow-up of 1 year to determine whether the patient's hypermetropia correction can maintain eye alignment after surgery. Prognosis of this the patient is still good even in the presence of strabismus amblyopia which is characterized by thesuppression of the left eye and the full correction spectacles showed no optimal visual acuity improvement [8][9]12].…”
mentioning
confidence: 99%
“…On the other hand, prisms have been used to reduce the amount of esodeviation and improve sensory status in partially accommodative esotropia (PAET) and acquired strabismus [8,13,14,34] . However, the long-term effect of prisms in reducing the angle of esodeviation in amblyopia has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that in patients with consecutive esotropia or partially accommodative esotropia, the use of base-out prisms regained binocular fusion, stimulated fusional divergence, and achieved orthophoria in a step-by-step manner to reduce prismatic strength [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%